2009
DOI: 10.1093/dnares/dsp005
|View full text |Cite
|
Sign up to set email alerts
|

Development of Genome-wide Simple Sequence Repeat Markers Using Whole-genome Shotgun Sequences of Sorghum (Sorghum bicolor (L.) Moench)

Abstract: Simple sequence repeat (SSR) markers with a high degree of polymorphism contribute to the molecular dissection of agriculturally important traits in sorghum (Sorghum bicolor (L.) Moench). We designed 5599 non-redundant SSR markers, including regions flanking the SSRs, in whole-genome shotgun sequences of sorghum line ATx623. (AT/TA)n repeats constituted 26.1% of all SSRs, followed by (AG/TC)n at 20.5%, (AC/TG)n at 13.7% and (CG/GC)n at 11.8%. The chromosomal locations of 5012 SSR markers were determined by com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
74
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(80 citation statements)
references
References 27 publications
4
74
1
1
Order By: Relevance
“…This is higher than EST-SSRs reported in wheat (25%), sorghum (45%) and cultivated flax (40.7%) (Eujayl et al 2002;Cloutier et al 2009, Yonemaru et al 2009), but lower than another study in L. usitatissimum (62.2%) (Roose-Amsaleg et al 2006). Differences in polymorphism might be attributable to the genomic origin of the SSRs developed by Roose-Amsaleg et al (2006) considered more polymorphic than EST-SSRs.…”
Section: Distribution Of Est-ssrs and Polymorphismcontrasting
confidence: 56%
“…This is higher than EST-SSRs reported in wheat (25%), sorghum (45%) and cultivated flax (40.7%) (Eujayl et al 2002;Cloutier et al 2009, Yonemaru et al 2009), but lower than another study in L. usitatissimum (62.2%) (Roose-Amsaleg et al 2006). Differences in polymorphism might be attributable to the genomic origin of the SSRs developed by Roose-Amsaleg et al (2006) considered more polymorphic than EST-SSRs.…”
Section: Distribution Of Est-ssrs and Polymorphismcontrasting
confidence: 56%
“…Lagercrantz et al (1993) reported the frequent occurrence of (AT) n motif among dinucleotides as the peculiar feature of most plant genomes. This is in accordance with the present study and other studies such as microsatellite detection in cpDNA of 12 Brassicaceae family members (Sumit et al 2010) and whole genome sequences of Sorghum bicolor (Yonemaru et al 2009) and pine genomic sequences (Chagne et al 2004).…”
Section: Ssr Distribution In Date Palm Genomesupporting
confidence: 94%
“…Compared to SNP marker system, SSR markers requires just the primer sequences which are usually available once published. This is the primary reason why so much effort has been devoted to developing SSR markers (Kong et al 2000;Li et al 2009;Ramu et al 2009;Srinivas et al 2009;Yonemaru et al 2009) and to using SSR markers in genetic mapping (Bhattramakki et al 2000;Haussmann et al 2002;Wu and Huang 2006), diversity studies (Abu Assar et al 2005;Agrama and Tuinstra 2003;Ali et al 2008;Anas and Yoshida 2004;Barnaud et al 2007;Caniato et al 2007;Casa et al 2005;Deu et al 2008;Dillon et al 2005;Folkertsma et al 2005;Ghebru et al 2002;Menz et al 2004;Pei et al 2010;Shehzad et al 2009b;Smith et al 2000;Wang et al 2009b) and molecular breeding (Knoll and Ejeta 2008) in sorghum. The objective of this study was to identify SSR markers associated with sorghum stem height using the aforementioned poolbased genome-wide association mapping technique.…”
Section: Introductionmentioning
confidence: 99%